Experimental study on effect of silica sand as partial fine aggregates replacement in epoxy polymer cement concrete - How, Han Zhen (2018)
Conventional concrete which is produced by the mixture of cement, coarse aggregates, fine aggregates, and water is less environmental friendly due to calcination and mining of sand in river and sea. Polymer concrete is thus promoted where the cement and fine aggregates are replaced partially within itself. In this study, mechanical properties such as compressive strength and tensile splitting strength are measured. The optimum percentage of conventional sand replaced with silica sand to achieve the highest tensile splitting strength can be obtained which is 20%. After 28 days of curing, the maximum tensile splitting strength of polymer cement concrete with 20% replacement level of conventional sand with silica sand increases up to 2.83%. For compressive strength, the strength gets lower when the percentage of fine aggregates replaced with silica sand is higher. After 28 days of curing, the maximum compressive strength of polymer cement concrete decreases up to 30% when the replacement level of fine aggregates is 60%. Silica sand can be used instead of conventional sand in certain parts of the building that do not take high loading since it is more environmental friendly. Concrete projects such as pathways, driveways, and playhouse floor that do not require reinforcement can be constructed by using polymer cement concrete as the uses of silica sand can also save more construction cost.